PEMBELAJARAN KETERAMPILAN MENYIMAK PADA SISWA KELAS VIII SMP NEGERI 3 SUNGAI KAKAP - Sari, Yanti Permata; Hanye, Paternus; Salem, Laurensius (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
Abstract        This research entitled learning skill of listening to students of class VIII SMP Negeri 3 Sungai Kakap. The general problem of this research is "How to learn listening skills to the students of grade VIII SMP Negeri 3 Sungai Kakap? The research method used in this research use qualitative research type with descriptive method. While the data collection tools used are observation, interview and documentation. The results of this study can conclude. Planning on learning listening in SMP Negeri 3 Sungai Kakap has been good in preparing the RPP in accordance with the curriculum 2013, where teachers plan learning listening learning is prepared using a scientific approach, in scientific approach consists of activities Observing, questioning, exploring, associating and communicating, in learning planning, teachers use learning strategies to convey learning listening in the form of role play strategy and using learning media in the form of video about learning listening.        Keywords: Learning Skills Listening, Grade VIII Students